PENGARUH PENGGUNAAN KODE WARNA PADA MAP REKAM MEDIS PASIEN TERHADAP PENCEGAHAN KEJADIAN MISFILED DI RUMAH SAKIT UMUM DAERAH (RSUD) KOTA BOGOR - Muhammad Irfan; Yuyun Yunengsih (Journal of Innovation Research and Knowledge, 2021)
Medical record is a file that contains notes and documents about the identity of the patient and all actions that have been given by medical personnel to the patient. The patient’s medical record must be protected by placing it in a folder or folder that is protected and there is a special section that is used to write the medical record number and paste the color code. The use of color coding on the medical record map file to prevent errors in storing and make it easier to find the wrong medical record. This study aims to determine the effect of using color coding on patient medical record folders on the prevention of misfiled events. This study uses a quantitative method with a descriptive approach. Data was collected by observation, questionnaires, and literature study. Based on the results of a simple linear regression test, it is known that there is an effect of using color codes on the prevention of misfield occurrences at the Bogor City Hospital by 54.4% while the remaining 45.6% is thought to be influenced by other factors that are not examined. It is recommended that medical recorders be more careful in installing color coded stickers on numbers 7 and 8 because the colors look similiar so that there are no errors in installation and making SOPs regarding the use of color codes on medical record folders.